2016
DOI: 10.1097/icl.0000000000000163
|View full text |Cite
|
Sign up to set email alerts
|

Use of Scleral Lenses and Miniscleral Lenses After Penetrating Keratoplasty

Abstract: Scleral lenses are effective and safe in patients who have had PK. There was a mean gain in visual acuity, with the majority of patients achieving 20/40 vision or better. The patient's subjective perception of vision was a significant factor in determining whether scleral lens wear was continued or abandoned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 23 publications
4
30
0
4
Order By: Relevance
“…In recent years, various studies have shown that scleral mirrors have great advantages for the treatment of ocular surface diseases. Barnett et al [29] reported the use of scleral mirror in 34 patients (48 eyes) with irregular astigmatism after PKP surgery, postoperative review of BCVA, 39.6% of the eyes reached 20/20 and above, 91.7% of the eyes reached 20/40 and above, and with no obvious complications, the results are similar to other scholars in this regard. Harthan [30] used a small scleral lens to treat Graves' eye disease.…”
Section: Scleral Mirrorsupporting
confidence: 73%
“…In recent years, various studies have shown that scleral mirrors have great advantages for the treatment of ocular surface diseases. Barnett et al [29] reported the use of scleral mirror in 34 patients (48 eyes) with irregular astigmatism after PKP surgery, postoperative review of BCVA, 39.6% of the eyes reached 20/20 and above, 91.7% of the eyes reached 20/40 and above, and with no obvious complications, the results are similar to other scholars in this regard. Harthan [30] used a small scleral lens to treat Graves' eye disease.…”
Section: Scleral Mirrorsupporting
confidence: 73%
“…Barnett and Lien reported that one third of ScCL wearers discontinued lens wear due to handling issues. 2 In another report, 25% of patients stated that the most common reason for abandoning ScCL wear was difficulty with application and removal 3 and 20% of patients had challenges with placement of lenses. 4 Other studies showed a much lower rate of abandoning ScCL due to handling problems.…”
Section: Discussionmentioning
confidence: 97%
“…1 Several studies report the common reasons for abandoning ScCL wear to be the difficulty with application and removal. [2][3][4] Whereas, other studies have debunked difficulties with ScCL handling. 1,[5][6][7][8][9][10][11][12] ScCL complications related to handling are rare and most are managed without any lasting side-effects.…”
mentioning
confidence: 99%
“…The fluid-filled device allows for healing of the corneal epithelium as well as masking of irregular corneal astigmatism improving best-corrected visual acuity. 64 , 65 Patients should be very closely monitored for signs of corneal edema and acute corneal graft rejection. In addition to careful slit lamp examination, evaluating baseline and follow-up corneal pachymetry and specular microscopy may be considered.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to careful slit lamp examination, evaluating baseline and follow-up corneal pachymetry and specular microscopy may be considered. 64 , 65 Normal endothelial cell density in a healthy adult patient is between 2000 and 2500 cells/mm 2 . The endothelium begins to decompensate when the cell count drops <500–1000 cells/mm 2 , leading to corneal edema, stro-mal haze, and reduced vision.…”
Section: Introductionmentioning
confidence: 99%